Isolation and expression of four Megalobrama amblycephala toll-like receptor genes in response to a bacterial infection. Issue 93 (October 2019) - Zhan, Fan-Bin; Tan, Kianann; Song, Xiaoran; Yu, Jiongying; Wang, Wei-Min
Abstract: Toll-like receptors (TLRs) are a category of pattern recognition receptors (PRRs), which recognize pathogen associated molecular patterns (PAMPs) and participate in the immune responses. We identified tlr5a, tlr5b, tlr9 and tlr21 from the genome of blunt snout bream ( Megalobrama amblycephala ). All four tlrs were constitutively expressed in all examined tissues. After an immune bacterial challenge with Aeromonas hydrophila, their expressionwas up-regulated in lymphoid organs and tissues. Recombinant eukaryotic plasmid pEGFP-N1 was transfected into the common carp ( Cyprinus carpio ) EPC (epithelioma papulosum cyprini) cells for the purpose of subcellular localization. pcDNA3.1(+) recombinant eukaryotic plasmid was used to investigate the effects of overexpression of tlrs on the expression of downstream interferon-associated immune factors. The four Tlrs were distributed in the cytoplasm of transfected cells and appeared as filamentous or reticular. The expression of irf3, irf7, isg15, mx1, pkr and viperin at 0, 6, 12, 18, 24, 36, 48 and 72 h post-transfection in transfected EPC cells was quantified by qPCR. Overexpression of tlrs upregulated the expression of viperin, isg15, irf3, irf7, mx1 and pkr (in that order of magnitude). We also cloned the following promoters of irfs : Irf1-p, irf2-p, irf6-p, irf7-p, irf8-p and irf9-p . Results of the dual luciferase reporter assay suggested that tlr5a, tlr5b and tlr9 enhanced the activities of irf7-p, while tlr5b enhanced the activities of irf1-p and irf7-p . This suggests that they all play a role in the innate immunity. The experiments also indicated that TLRs activate irf3 or irf7 signaling to induce IFN secretion and subsequent upregulation of IFN-stimulated genes. These results indicate that tlrs and irfs play an important immune role in response to A. hydrophila infection in blunt snout bream, and pave the way for further studies of immune mechanisms mediated by TLRs in fish. Highlights: tlr5a, tlr5b, tlr9 and tlr21 cDNA were cloned from Megalobrama amblycephala . tlrs from M. amblycephala are constitutively expressed in a wide range of tissues in vivo. Aeromonas hydrophila infection alters the mRNA expression of tlrs . Overexpression of tlr genes upregulated the expression of irf3, irf7, isg15, mx1, pkr and viperin . Cloned six promoters of irfs in M. amblycephala and tlr5a, tlr5b and tlr9 enhanced the activities of irf7-p .